Plio-Pleistocene paleoenvironmental evolution of the intermontane Humahuaca Basin, southern Central Andes. (November 2021) - Galli, Claudia I.; Alonso, Ricardo N.; Amorós, Elisabet Beamud; Pingel, Heiko; Eveling, Emilio; Coira, Beatriz L.; Stockli, Daniel F.; González, David
Abstract: Sedimentary records of Plio-Pleistocene intermontane basins of the Eastern Cordillera and the adjacent Puna Plateau in the Central Andes of NW Argentina (hinterland basins) are important geological archives that provide spatiotemporal insights into regional tectonism, the uplift history of basin-bounding mountain ranges, and associated depositional and paleoenvironmental changes. Here, we reconstruct the Plio-Pleistocene evolution of the intermontane Humahuaca Basin based on the study of depositional systems, unconformities, accumulation rates, depositional patterns, U–Pb geochronology, magnetostratigraphy, and sediment provenance of the Uquía Formation – a ca. 4.8–1.5-My-old sedimentary basin record consisting of a 100–400 m thick fining-upward stack of conglomerates, sandstones, and siltstones with intercalated volcanic tuffs. The sedimentary facies of the Uquía Formation comprise debris flow, deep sandy gravel braided alluvial fan deposits, sheetflood dominated, floodplains, and shallow ephemeral lake deposits. Facies characteristics and δ 18 O and δ 13 C values from pedogenic and palustrine carbonates indicate freshwater lacustrine conditions at the base and evaporative conditions towards the top of the Uquía Formation (ca. 2.3 Ma). During the deposition of the Uquía Formation, the Humahuaca Basin was already bounded by uplifted mountain ranges: (a) the Sierra Alta to the west, which experienced early uplift during the middle Eocene and increased exhumation from about 15 to 10 Ma; and (b) the Aparzo and Tilcara ranges to the east, whose deformation and uplift began about 15–10 Ma and culminated in the structural and fluvial separation of the Humahuaca Basin from the foreland by ca. 4.8 Ma in the center and by about 4.2 Ma in the southern sector of the basin. This is supported by variable unroofing patterns, the paleoenvironmental evolution, deposition of sheetflood dominated alluvial fans, and lacustrine deposits. Graphical abstract: Image 1 Highlights: Model of paleoenvironmental evolution of the intermountain Humahuaca Basin. δ 13 C and δ 18 0 trends suggest a changeover from an open towards a closed lake system. Zircon U–Pb ages from intercalated tuffs refine basin chronologies and correlation. Used magnetostratigraphy to date the base of section of Uquía Formation.